Pengembangan Assesment Pembelajaran Pendidikan Agama Islam pada Lembaga Pendidikan Vokasi Islam di Era Digital - Baihaki, Mahfud; Paramansyah, Arman (Sekolah Pascasarjana Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
The purpose of this study is to find out the efforts to develop an assessment of Islamic learning in Islamic vocational education institutions in the digital era. The method used in this study uses a qualitative method with a descriptive analysis approach through library research. The results of the study can be concluded that the development of an assessment of Islamic Education learning in Islamic vocational institutions in the digital era 1) Attempts to develop and evaluate learning for the progress of students by carrying out a comprehensive assessment process. 2) The vision and mission reflect the excellence that educational institutions want to inculcate, and the main objectives focus on three things, namely skills, religion and character education. 3) Evaluation results to promote digital technology advances and understand Islamic religious principles. 4) Aiming for professionalism in the digital era both in terms of knowledge and characteristics. Keywords: Assessment, Islamic Religious Education, Vocational, Digital Era.